2013
DOI: 10.1507/endocrj.ej12-0241
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of insulin sensitivity promotes extravillous trophoblast cell migration stimulated by insulin-like growth factor-I

Abstract: Insulin-like growth factor-I (IGF-I) has been shown to stimulate extravillous trophoblast (EVT) cell migration and invasion, and to play a crucial role in placental function, thereby, influencing placental development and fetal growth. Insufficient invasion of EVT cells into the uterine endometrium leads to pregnancy-related complications, including spontaneous abortion, fetal growth restriction (FGR), and pregnancy-induced hypertension (PIH). Insulin-resistant conditions such as polycystic ovary syndrome (PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Hyperphosphorylation of maternal plasma IGFBP-1 may serve as a novel early biomarker of IUGR. These observations are consistent with the possibility that IGFBP-1 phosphorylation constitutes a link between decreased decidual oxygen and nutrient availability and reduced fetal growth, mediated by diminished IGF-I bioavailability, resulting in inhibition of trophoblast invasion [125,148,149] and placental function (Figure 4).…”
Section: Mechanistic Tor Functions As a Decidual Nutrient Sensor And supporting
confidence: 85%
“…Hyperphosphorylation of maternal plasma IGFBP-1 may serve as a novel early biomarker of IUGR. These observations are consistent with the possibility that IGFBP-1 phosphorylation constitutes a link between decreased decidual oxygen and nutrient availability and reduced fetal growth, mediated by diminished IGF-I bioavailability, resulting in inhibition of trophoblast invasion [125,148,149] and placental function (Figure 4).…”
Section: Mechanistic Tor Functions As a Decidual Nutrient Sensor And supporting
confidence: 85%
“…; Mayama et al . ). However, IGF2 may also signal via IGF2R and G i proteins, MAPK and Rho GTPase pathways to trigger trophoblast migration and invasion (McKinnon et al .…”
Section: Introductionmentioning
confidence: 97%
“…Insufficient extravillous trophoblast invasion of the endometrium has been reported to cause pregnancy-associated complications, including miscarriage, pregnancy-induced hypertension and fetal growth restriction (36). Moreover, the migration and invasion of trophoblast cells has been suggested to be associated with insulin resistance (37). The results of the present study suggested that miR-345-3p expression decreased in GDM maternal placenta tissue and blood.…”
Section: Discussionmentioning
confidence: 47%